Robust Distributed Reprogramming Protocol of Wireless Sensor Networks for Healthcare Systems - Kuo-Yu Tsai (International Journal of Distributed Sensor Networks)
With the development of the wireless communication technologies, the wireless sensor networks (WSNs for short) are considered as one of the key research areas in healthcare systems. However, there is sometimes a need for removing bugs or adding new functionalities after WSNs are deployed. Wireless reprogramming is a process for propagating a new code image or relevant commands to sensor nodes in WSNs. In this paper, we propose a robust distributed reprogramming protocol of WSNs for healthcare systems, in which the security requirements are proved to be secure based on the elliptic curve discrete logarithm problem, such as existential unforgeability of signature for code image, authenticity of code image, freshness, and node compromised tolerance.